"Study of Antiamoebic Antibody in Amoebiasis Using ELISA and RID Techniques" - N Arianpour; TM Mohapatra (Tehran University of Medical Sciences, 2003)
To study the humoral immune response to Entamoeba histolytica infection, sera prepared from different cases of amoebiasis from gastroenterology ward of B.H.U hospital, including15 cases with amoebic liver abscess (ALA), 10 cases with acute amoebic dysentery (AD) and 10 controls were examined by Enzyme Linked Immuno Sorbent Assay (ELISA), using crude amoebic antigen prepared from Entamoeba histolytica NIH: 200 grown axenically and its three chromatographed fractions, i.e.fraction I (FI), fraction II (FII) and fraction III (FIII). Efficacies of different antigens in detecting anti amoebic antibodies were compared. Estimation of immunoglobulin G (IgG), immunoglobulin M (IgM) and immunoglobulin A (IgA) levels were also carried out employing Single Radial Immuno Diffusion (RID) technique. The results indicated that crude amoebic antigen and fraction I (FI) were more efficient in antibody detection while, potencies of fraction II (FII) and fraction III (FIII) were lower as antigens for serodiagnoses. On estimating different immunoglobulin levels, it was found out that there was significant increase in IgG level in amoebiasis group while, no significant increase was observed in IgA level. IgM level was increased only in amoebic liver abscess cases compared to negative controls.